The role of art education in fostering interdisciplinary learning - Lucero Garcés, Marco Fabián; Montejo Rodríguez , Erley; Coca Naranjo, Mónica Elisabeth; Reyes Benitez , Anderson Fernando (Arandu UTIC, 2025)
This study was conducted at the Pedro Fermín Cevallos Educational Unit with the aim of analyzing the impact of art education on interdisciplinary learning, based on the perceptions of teachers, students, and parents. A qualitative and quantitative methodology was used, including surveys and semi-structured interviews, to gather data on the experiences and opinions of the participants. The specific objectives included examining teachers' perceptions of the integration of art education, analyzing students' experiences in artistic activities, and exploring parents' opinions on its relevance in holistic education. The findings revealed that most teachers positively value art education as a means to foster interdisciplinary competencies, while students reported a better understanding of concepts in other subjects through these activities. However, some teachers and parents expressed concerns about the potential deprioritization of art education due to pressure to meet standardized assessments. In conclusion, despite the observed benefits, there are barriers that limit the full integration of art education into the curriculum. It is essential to promote closer collaboration among teachers, families, and administrators to ensure that art education is valued and supported as an essential component of interdisciplinary learning, thereby guaranteeing a more comprehensive and enriching educational experience.